YOGIC MANAGEMENT FOR MENSTRUAL DISORDERS - Acharya Trupti Dyaniee; Mishra Sangeeta Shyammurti; Sharma Vikas (International Journal of Applied Ayurved Research, 2016)
A woman of child bearing age should menstruate every 28 days or so unless she is pregnant or moving into menopause. But numerous things can go wrong with normal pubertal development, menstrual cycle, pregnancy and menopause, some the result of psycho-somatic-factor, undeveloped secondary sexual character, abnormal anatomical and functional aspect of reproductive organs, endocrinal factors etc. These are produced due to heavy workouts, sudden loss in weight, changes in diet pattern and mode of life, excessive stress, and such activities bring about a lot of changes in a women’s body. So yoga is one of the illustrious ways to cure menstrual disorders. In this paper researchers discuss all the points’ related to yoga & menstrual disorder